A Rare Case of Neurosyphilis with Calvaria Osteitis Presenting in Pregnancy - Gisella M. Newbery; Christine E. Henricks; Julie A. Vircks; Andreina Colina; David C. Mundy (Case Reports in Obstetrics and Gynecology)
Background. The incidence of syphilis throughout the world is increasing. Rates in pregnancy are similarly rising, presenting risks of an untreated syphilis infection that can be detrimental to the mother and fetus. Although routine screening for syphilis infections is recommended at the initial prenatal visit, there is a lack of universal agreement on rescreening pregnant people and approximately 50% of syphilis cases are asymptomatic in the general population. Furthermore, some symptoms of syphilis can overlap with nonspecific pregnancy-related symptoms. Meanwhile, Treponema pallidum can spread to various maternal and fetoplacental tissues quickly after infection and occur at any stage of syphilis. Case. A 26-year-old gravida 5 para 2 presented with a new onset headache and visual and auditory changes at 23 weeks of gestation. A computerized tomography scan revealed numerous ill-defined lytic lesions throughout the calvarium, suspicious for syphilitic osteitis. She tested positive for syphilis antibodies with a rapid plasma reagin (RPR) titer of 1 : 32. Cerebrospinal fluid evaluation from a lumbar puncture resulted in reactive fluorescent treponemal antibody (FTA) testing. She was diagnosed with secondary syphilis with osteitis and neuro and otic components. She completed 14 days of intravenous aqueous crystalline penicillin G with additional benzathine penicillin G 2.4 million units intramuscular weekly for two weeks. There was no evidence of congenital syphilis on neonatal examination. Conclusion. Syphilitic osteitis and neuro, otic, or ocular syphilis infections occur rarely in the nonpregnant population, and therefore, little data in pregnancy is available to inform outcomes in these specific disease states. It is of paramount importance to complete appropriate syphilis screening, recognize symptoms, and consider utilizing rescreen protocols to ensure prompt infection identification and treatment. For neuro, otic, and ocular syphilis, aqueous crystalline penicillin G (as opposed to benzathine penicillin G) is required to achieve treponemicidal concentrations in those physiologic compartments. There is no agreement as to the appropriate treatment regimen for the rare finding of syphilitic osteitis.